On path length, beam divergence, and retroreflector array size in open-path FTIR spectroscopy - C. E. N. Power; C. E. N. Power; A. Wiacek; A. Wiacek (Atmospheric Measurement Techniques)
Open-path Fourier transform infrared (OP-FTIR) spectroscopy is an established technique used to measure boundary layer trace gas concentrations, consisting (in this work) of a spectrometer with an active mid-IR source coupled to a single transmitting and receiving telescope, as well as a cube-corner retroreflector array separated from the spectrometer and telescope by an atmospheric path. The detection limit at first increases with increasing optical path length (OPL) in the atmosphere, which controls target gas spectral absorption depth; however, open-path beam divergence can lead to overfilling of the distant retroreflector array for separations greater than ∼ 150 m (OPL ∼ 300 m; the details depend on specifics of spectrometer and telescope optics, plus array size), resulting in decreased returning radiation at the detector. In this case, the absorption signature of the target gas increases, but the signal-to-noise ratio of the recorded spectrum decreases. We present the results of theoretical spectral simulations for formaldehyde (HCHO) that show how path length, interfering water concentration, and HCHO target concentration affect the expected differential absorption spectrum of the HCHO target at 1 ppb. HCHO serves as a proxy for any low-abundance trace gas with relatively weak absorption features, which makes it sensitive to changes in the performance and setup of the OP-FTIR system, as explored in this study. We demonstrate that optical path lengths >∼<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="19pt" height="9pt" class="svg-formula" dspmath="mathimg" md5hash="7eb8b78e0c2c82595de8834cea1f4483"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-2537-2025-ie00001.svg" width="19pt" height="9pt" src="amt-18-2537-2025-ie00001.png"/></svg:svg> 300 m are necessary for robust HCHO spectral signatures (at our typical random plus systematic noise levels). Next, we present the results of two field experiments where the retroreflector array area was increased to collect a larger fraction of returning radiation, at two-way path lengths ranging from 50 to 1300 m. We confirm that the larger retroreflector array resulted in a slower decrease in the signal as a function of optical path length. Finally, we perform retrievals of HCHO concentrations from spectra collected at the same field site and path length in Halifax Harbour during 2018 and 2021, with a smaller and a larger retroreflector array, respectively. We demonstrate that retrievals based on larger retroreflector array spectra exhibit ∼<mspace width="0.125em" linebreak="nobreak"/>2×<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="a63aadb6c09e79daa7c5681a193ce68a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-2537-2025-ie00002.svg" width="29pt" height="10pt" src="amt-18-2537-2025-ie00002.png"/></svg:svg> higher precision (average standard deviation in hourly formaldehyde data bins over 2 d), even though systematic errors remain in the fitted spectra, due to water vapour. Where systematic fitting errors in interfering species (e.g., water) are significant, a longer path may not be optimal for a given target gas, leading instead to biased retrievals; moreover, at very long optical path lengths the signal-to-noise ratio decreases with increasing water vapour due to broadband mid-IR spectrum signal reduction in water-saturated regions. We discuss factors to consider in the choice of path length and retroreflector array size in open-path FTIR spectroscopy, which must be made with care.